Inequality, fairness and social capital - Fehr, Dietmar; Rau, Hannes; Trautmann, Stefan T.; Xu, Yilong (Discussion paper series, 2018)
Abstract: We study the impact of unjust inequality on social trust and trustworthiness, and its separate effect on the economically successful and the unsuccessful, in a controlled economic experiment. We find evidence for a negative effect of unfair economic inequality on social interactions. Probing the boundaries of this effect, we document that this erosion of social capital critically depends on the context: if a well-off person is not directly responsible for the outcome of the worse-off person, then we observe no negative effects on trust and trustworthiness in the aggregate. Moreover, our data do not support the view that higher status or wealth leads to an erosion of pro-social attitudes: the successful are always more generous; groups of unsuccessful persons are least efficient and least generous in the trust game.
Keywords: inequality, fairness, social capital, JEL classifications C91, D31, D63
Keywords: Graue Literatur